Evaluation of chemical composition and in vitro digestibility of stovers of different pearl millet varieties and their effect on the performance of sheep in the West African Sahel - Umutoni, Clarisse; Bado, V.; Whitbread, Anthony M.; Ayantunde, Augustine A.; Gangashetty, P. (Informa UK Limited, 2021)
The objective of this study was to assess the chemical composition and in vitro digestibility of residues of five pearl millet varieties and to investigate their effect on the performance of sheep. Thirty castrated male Bali-Bali sheep were randomly assigned to five treatments. Four dual-purpose millet varieties and one local variety-Somno were used. Sheep were fed ad libitum for 90 days with the stover of five millet varieties, complemented with cowpea hay. Stover of varieties ICMV167005 and ICMV167002 showed a tendency for a higher nitrogen content (1.0%) and in vitro digestibility (51.3% and 51.8%, respectively) compared to stover of other varieties. Significant differences were observed in average daily live weight gain. The animals fed with stover of the variety ICMV167005 in their diet had higher average daily live weight gain compared with others. We conclude that ICMV167005 is a promising variety for improving the productive performance of sheep.